Analysis of the impacts of Spanish agriculture on climate change Evolution of the emission of Greenhouse Gases 1990-2005 (Revista LIDER, 2020)
Over the past 50 years agriculture has suffered serious environmental problems such as desertification, increased carbon dioxide emissions (CO2) and other greenhouse gases, the decline of biodiversity and water pollution. This article aims to analyze the evolution of the indicators of emission of greenhouse gases in Spain between 1990-2005, in order to identify the main trends of agriculture on climate change globally.